Frontispiece: Alkyliodines in High Oxidation State: Enhanced Synthetic Possibilities and Accelerated Catalyst Turn‐Over. Issue 60 (28th October 2019) - Bosnidou, Alexandra E.; Muñiz, Kilian
Abstract : Did Conrad Willgerodt and Johannes Thiele ever personally meet to discuss iodine(III) chemistry? In the end, Freiburg and Strasbourg are located quite near to each other. At such a hypothetical meeting, the two pioneers of "polyvalent iodine chemistry" would probably have celebrated their discovery of aryl and alkyl iodine(III) derivatives. Whereas the commonly stable aryliodine(III) compounds have become an ubiquitous class of reagents in organic synthesis, the corresponding alkyliodine(III) compounds are of notorious instability. The Concept Article by A. E. Bosnidou and K. Muñiz on page 13654 ff., provides an overview on the status quo of alkyliodine(III) compounds as practical reagents and catalyst states in organic transformations and on the prospects for future developments in the field.